Inovasi Pasta Farfalle dengan Pemanfaatan Tepung Kedelai Mocaf dan Daun Jelatang (Urtica dioica L) - Bima Muhammad Pembayun; Ita Fatkhur Romadhoni; Lilis Sulandari; Nugrahani Astuti (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Pasta farfalle in this study is a processed product made from pasta (wheat flour, eggs, water, oil, salt) soybean flour, mocaf and nettle leaves processed by drying and boiling techniques. Ribbon-shaped and jagged, which served as complementary foods. The purpose of this product is 1) to determine the organoleptic properties that include shape, color, aroma, taste and texture, 2) to determine the nutritional content of soy flour farfalle paste, mocaf and nettle leaves. The data collection technique used was observation through 5 trained panelists and 25 semi-trained panelists assisted by observation sheets scoring 1-5. The independent variables in this study are soy flour and mocaf, the dependent variables in the study are the shape, color, aroma, taste and texture, and the control variables of this study are the tools used, materials of manufacture, and manufacturing techniques. Data analysis in this study showed 1) there is no influence of color, aroma, and taste, 2) there is an influence of shape and texture of pasta products farfalle.